Hyperspectral Remote Sensing Applications in Agriculture - Navya, K.; Niharika, M. (Chronicle of Bioresource Management, 2025)
Remote sensing satellites offer diverse data across the panchromatic, multispectral, and hyperspectral optical ranges, each with distinct capabilities. Hyperspectral sensors, in particular, capture over 100 contiguous spectral bands within a narrow 5–10 nm bandwidth, spanning wavelengths from 500 to 2500 nm. This high spectral resolution provides detailed information for accurate material identification, making hyperspectral imaging a powerful tool for mapping land resources. Unlike multispectral datasets, which cover fewer bands and have broader bandwidths, hyperspectral imaging can distinguish between similar spectral features, allowing for more precise analysis. This advanced imaging approach combines modern imaging systems with traditional spectroscopy, facilitating detailed assessments of soil, vegetation, and water quality. However, due to limited access beyond the scientific community and high costs, hyperspectral imaging has yet to see widespread adoption in fields like precision agriculture, where it could significantly enhance crop monitoring, disease detection, and resource management.